2015
DOI: 10.1080/21645515.2015.1066946
|View full text |Cite
|
Sign up to set email alerts
|

Safety, immunization coverage and determinants of a new kind of Hepatitis B vaccine firstly applied in Ningbo, China

Abstract: Evaluate safety and immunization coverage of a new kind of recombinant Hepatitis B vaccine (HepB) in Ningbo city, China. Two groups were carried out in 2 of 11 randomly selected countries in Ningbo in 2009. All of the infants born from July 1 to December 31, 2009 were enrolled as subjects and received 3 doses of HepB at 0, 1, 6 month. Control group (N D 3452) received current HepB derived from Saccharomyces Cerevisiae Yeast (HepB made by recombinant DNA techniques in Saccharomyces Cerevisiae Yeast, HepB-SCY; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Although there had been a great improvement in infant Hep B coverage, this study showed that certain groups remained at high risk of not receiving a timely birth dose or full immunization. This was consistent with previous reports from other provinces of China [4,14,15,16,17], and was attributed to risk factors such as uneven economic development, rural areas, and ethnic minorities. Other reports from some developing countries attributed the delayed or incomplete Hep B vaccination to the poor practice of the vaccination service [18,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…Although there had been a great improvement in infant Hep B coverage, this study showed that certain groups remained at high risk of not receiving a timely birth dose or full immunization. This was consistent with previous reports from other provinces of China [4,14,15,16,17], and was attributed to risk factors such as uneven economic development, rural areas, and ethnic minorities. Other reports from some developing countries attributed the delayed or incomplete Hep B vaccination to the poor practice of the vaccination service [18,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…Secondly, we confirmed that the vaccines were transported by cold-chain logistics and they were still under guarantee. Thirdly, all vaccines in this study were expressed in Hansenulapolymorpha, which has been routinely administered to infants at birth, and the Global Advisory Committee on Vaccine Safety has also confirmed its safety (Das et al, 2019;Yang et al, 2015). Finally, we came to the factor of weight.…”
Section: Discussionmentioning
confidence: 90%